Cardiac Specific Knockout of p53 Decreases ER Stress-Induced Mitochondrial Damage - Chen, Qun; Thompson, Jeremy; Hu, Ying; Das, Anindita; Lesnefsky, Edward J. (Frontiers in Cardiovascular Medicine, 2019)
Endoplasmic reticulum (ER) stress contributes to cardiovascular disease including heart failure. Interactions between the ER and mitochondria during ER stress can impair the mitochondrial respiratory chain and increase cell injury. p53 is a tumor suppressor protein that regulates apoptosis. p53 contributes to the regulation of mitochondrial and ER interactions, especially during the progression of ER stress. The knockout (KO) of p53 leads to decreased injury in hearts following ischemia-reperfusion. We asked if KO of p53 can protect mitochondria during the induction of ER stress and decrease cell injury. Floxed p53 mice were crossed with mice carrying an α-myosin heavy chain cre to generate cardiac specific p53 KO mice. Thapsigargin (THAP) was used to induce ER stress in wild type (WT) and p53 KO mice. Mice were euthanized after 48 h THAP treatment. Cardiac mitochondria were isolated for functional measurement. TUNEL staining was used to assess myocyte death. In WT mice, THAP treatment decreased the rate of oxidative phosphorylation using pyruvate + malate as complex I substrates compared to vehicle-treated control. Complex I activity was also decreased in the THAP-treated WT mice. The rate of oxidative phosphorylation and complex I activity were not altered in THAP-treated p53 KO mice. The content of pyruvate dehydrogenase (PDH) α1 subunit was decreased in THAP-treated WT mice but not in p53 KO mice. ER stress led to a release of cytochrome c and apoptosis inducing factor from mitochondria into cytosol in WT but not in KO mice. Knockout of p53 also preserved mitochondrial bcl-2 content in THAP-treated mice. In WT mice, THAP treatment markedly increased cell death compared to vehicle treated hearts. In contrast, cell injury was decreased in THAP-treated p53 KO mice compared to corresponding wild type. Thus, KO of p53 decreased cell injury by protecting mitochondria during the ER stress.